ENZYMATIC HYDROLYSIS OF THE FEC 25 AND ROTI CASSAVA STARCH (Manihot esculenta) VARIETIES BY α-AMYLASE FROM A MARINE BACTERIUM (BREVIBACTERIUM SP.) - rahmani, nanik; Andriani, Ade; Hartati, Sri; Yopi, Yopi (LIPI Press, 2016)
Cassava (Manihot esculenta) is one of the food sources that is familiar for Indonesian society. Carbohydrates of cassava can be enzymatically hydrolyzed into small oligosaccharides that can be used as a material for functional food components production. Starch from the FEC 25 and roti cassava starch have been hydrolyzed by α-amylase from marine bacterium, Brevibacterium sp. for maltooligosaccharides production. The best hydrolysis reaction condition of the FEC 25 cassava starch were starch concentration of 6.0% (w/v), the ratio of α-amylase and starch 1:1, 50 mM of sodium phosphate buffer pH 6.6, the reaction temperature at room temperature (30oC) and the reaction time of 8 hours with the highest reducing sugar value of 21.675 ppm. While the best hydrolysis of the Roti cassava starch were starch concentration of 6% (w/v), the ratio of α-amylase and starch 1:1, 50 mM of sodium phosphate buffer pH 6.6 and the reaction temperature at 50oC, the reaction time of 8 hours with the highest reducing sugar value of 13.278 ppm. The results of maltooligosaccharides analysis using thin layer chromatography (TLC) showed that the type of maltooligosaccharides formed on hydrolysis the FEC 25 cassava starch are glucose, maltose and maltotriosa, while Roti cassava starch are glucose, maltose, maltotriose, and maltopentaose. The formation of maltooligosaccharides showed that both of cassava starch can be hydrolyzed by α-amylase from marine bacterium Brevibacterium sp.